Pembayaran Zakat Dan Pajak Di Negara Hukum Pancasila - Cucu Solihah (Syiar Hukum, 2017)
Religian and law are two unseparated notions from Indonesia as a state and nation. In Indonesia moslems are the majority and they are obliged to follow a certain law taken from their religion and it has been considered as positive law. Therefore, the state plays strategic role to organize laws taken from religion as zakat law by issuing law Number 23 year 2011 about zakat management. Besides, Indonesian citizen is also obliged to pay the tax. In order to avoid those 2 (two) obligations then the law number 36 year 2008 about the forth change of law number 7 year 1983 about income tax.